EFFORTS TO PREVENT DIVORCE BY JUDGES AT THE BARRU RELIGIOUS COURT (PERMA ANALYSIS NUMBER 1 OF 2016 CONCERNING MEDIATION PROCEDURES IN COURTS) PERSPECTIVE OF ISLAMIC LAW - Azizah, Nurul; Sultan, Lomba; Azra, Azni (International Journal of Islamic Studies, 2021)
Overview Divorce cases at the Barru Religious Court have increased significantly from year to year, increasing by around 20% each year, the majority being filed by the wife. the factor that causes the majority is the existence of continuous disputes and quarrels followed by reasons to leave one of the parties, while the other reasons are only a small part. Efforts to prevent divorce by judges at the Barru Religious Court in the form of mediation have been in line with the provisions of Perma No. 1 of 2016 concerning Mediation, at each stage of mediation various efforts have been carried out, including: at the Pre-Mediation stage, Advisory was carried out by the Panel of Judges Examining the Case, at the Mediation stage, efforts were made in the form of: a. Creating a comfortable and conducive atmosphere, sometimes accompanied by jokes, b. Actively listen to the problems expressed by each party, c. Responding and clarifying the intentions of the parties and bridging the differences between the two, d. Conducting Caucus, e. Show appreciation, and at the Final stage of Mediation, the Panel of Judges gives advice again at each trial. Efforts to prevent divorce by judges at the Barru Religious Court in the form of implementing mediation in the perspective of Islamic law have also been in line with the concepts of Islah and Hakam, and are also in accordance with the Maqasid Syariah principle, namely hifdz al-nasl (keeping offspring).